2010
DOI: 10.3168/jds.2010-3481
|View full text |Cite
|
Sign up to set email alerts
|

Herd-level prevalence of Johne's disease in Utah and adjacent areas of the intermountain west as detected by a bulk-tank milk surveillance project

Abstract: The objectives of this study were to estimate the dairy herd-level prevalence of Johne's disease (JD) in Utah and nearby areas of the intermountain west and to estimate the sensitivity of a single bulk-tank milk test for JD detection. Two milk samples from all bulk tanks on the study farms were collected 1 mo apart. Samples were frozen and shipped to a laboratory for JD testing. An ELISA to measure total IgG antibody specific against Mycobacterium avium ssp. paratuberculosis, the etiological agent that causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…The Parachek commercial ELISA tests have been found to have a high specificity and a sensitivity ranging from 21 to 67% on individual milk samples [8]. When used on bulk tank milk, the Pourquier ELISA test had a sensitivity of 57% [9]. Additionally, van Weering et al [10] demonstrated that certified MAP-negative herds had a low sample/positive (S/P) ratio on bulk milk Pourquier ELISA tests and they showed that the likelihood of a herd having a MAP-infected animal increased with increasing bulk milk ELISA S/P ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The Parachek commercial ELISA tests have been found to have a high specificity and a sensitivity ranging from 21 to 67% on individual milk samples [8]. When used on bulk tank milk, the Pourquier ELISA test had a sensitivity of 57% [9]. Additionally, van Weering et al [10] demonstrated that certified MAP-negative herds had a low sample/positive (S/P) ratio on bulk milk Pourquier ELISA tests and they showed that the likelihood of a herd having a MAP-infected animal increased with increasing bulk milk ELISA S/P ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The antibody prevalence of MAP was estimated as 10% by serum ELISA from previous sets of unpublished data from the QIA. Based on this estimated prevalence, the sample had to consist of at least 138 herds in order to obtain a relative of 5 percent with 95% confidence (Wilson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Using the same tests as in the current study, the same dairy region was surveyed previously for JD in 2009, with 67/170 (39%) of dairy herds detected with JD [32]. However, the previous study collected 2 samples from every bulk tank while the current study collected 5 samples per tank.…”
Section: Johne's Disease Prevalence Changes Over Timementioning
confidence: 99%
“…At Antel BioSystems, 2 separate analyses were performed on each bulk tank sample as previously described [32,34]. Briefly, each bulk tank sample was analyzed for MAP-specific IgG antibody by ELISA and for presence of MAP organism by real-time PCR.…”
Section: Testing For Map In Bulk Tank Milk Samplesmentioning
confidence: 99%
See 1 more Smart Citation